Ontological and epistemological foundations of qualitative research - Vasilachis, Irene (2009)
The purpose of this paper is to describe the most relevant features of qualitative research in order to show how, from the Epistemology of the Known Subject perspective I propose, it is necessary to review first the ontological and then the epistemological grounds of this type of inquiry. I begin by following the path that leads from the Epistemology of the Knowing Subject to the Epistemology of the Known Subject, proposed as a new and non exclusive way of knowing. I pass on to describe the primary and secondary characteristics of qualitative research, expressing the need for an ontological rupture. Finally, cognitive interaction and cooperative knowledge construction are considered as two fundamental features in the process of qualitative research grounded on the Epistemology of the Known Subject.